Weed management in maize (Zea mays ) in western Indo-Gangetic Plains through tank-mix herbicide application - SUSHA, V S; DAS, T K; SHARMA, A R (The Indian Journal of Agricultural Sciences, 2014)
To evaluate the bio-efficacy of pre-emergence tank-mix and sequential application (pre-emergence followed by (fb) post-emergence) of herbicides on weeds particularly Cyperus rotundus L. in maize (Zea mays L.), a field experiment was conducted in 2010 and 2011 at the Indian Agricultural Research Institute, New Delhi. It was observed that the tank-mix pre-emergence application of pendimethalin 0.75 kg/ha + imazethapyr 0.050 kg/ha with or without KNO3 (6%) and pendimethalin 0.75 kg/ha + chlorimuron-p- ethyl 0.006 kg/ha resulted in significant suppression of Cyperus rotundus, broad leaved and grassy weeds, and caused a significant reduction in total weed population and dry weight. These tank-mixes were superior to other weed control treatments and resulted in higher weed control efficiency and weed control index. However, the pre-emergence tank-mix application of pendimethalin 0.75 kg/ha + imazethapyr 0.050 kg/ ha resulted in comparable maize yield with weed-free check in both years, but the yields in this treatment were higher than in other weed control treatments. This treatment, excluding weed-free check, resulted in the highest net returns and net benefit:cost. Atrazine 1.0 kg/ha + mustard residue mulch @ 5 tonnes/ha was the next best treatment, resulting in higher maize yield through concurrent reduction in weed competition.